2021
DOI: 10.3389/fpsyg.2021.665419
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan Alters Brain Functional Network Plasticity and Promotes Cognitive Flexibility

Abstract: Objective: This study used resting-state functional magnetic resonance imaging to investigate the effects of 8 weeks of Tai Chi Chuan and general aerobic exercise on the topological parameters of brain functional networks, explored the advantages of Tai Chi Chuan for improving functional network plasticity and cognitive flexibility, and examined how changes in topological attributes of brain functional networks relate to cognitive flexibility.Methods: Thirty-six healthy adults were grouped into Tai Chi Chuan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 60 publications
(81 reference statements)
2
35
0
Order By: Relevance
“…Compared with TCC, BW is a relatively simple and repetitive movement with a single movement form. Our previous research on cognitive flexibility yielded similar results (Cui et al, 2021 ), suggesting that the improvement of cognitive function in young adults might require movement involving more cognitive operations. On the other hand, this finding may be related to the cycle of exercise, which lasted for 8 weeks in this experiment.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Compared with TCC, BW is a relatively simple and repetitive movement with a single movement form. Our previous research on cognitive flexibility yielded similar results (Cui et al, 2021 ), suggesting that the improvement of cognitive function in young adults might require movement involving more cognitive operations. On the other hand, this finding may be related to the cycle of exercise, which lasted for 8 weeks in this experiment.…”
Section: Discussionsupporting
confidence: 71%
“…For facial perception, the exercise intervention in this study was set in the form of a group, which inevitably involved facial recognition and perception, which might also be one of the reasons for improving its effects. The enhancement of fALFF in the FFG.R by TCC might be caused by the elements of mindfulness and meditation contained in the TCC (Cui et al, 2021 ). Furthermore, it has been found that TCC can improve levels of mindfulness (Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations